Evaluation of cooking and sensory attributes of selected South Indian rice land races - Chitra Kalaichelvan*, S.Babu (International Journal of Advanced Science and Technology, 2020)
There is an increased interest in usage of traditional rice landraces amongst the educated urban population of South India due to its varied health benefits. The current study was undertaken with nineteen parboiled rice landraces available in South India along with White Ponni (a popular hybrid variety of Taichung65 and Myang Ebos 6080/2) as the control. Cooking characteristics and sensory evaluation of these varieties were studied. The results showed that the traditional landraces are liked by the sensory panel. Besides, the texture analyser attributes of the rice land races were comparable with that of the White Ponni. The cooking trails revealed that most of the landraces tested had similar cooking time when compared with the control. A few landraces had similar volume of expansion as that of White Ponni.